1982
DOI: 10.1364/ol.7.000460
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic desensitization of single-mode fibers utilizing nickel coatings

Abstract: The pressure sensitivity of the phase of light propagating in a single-mode fiber coated with a thin nickel jacket is determined both analytically and experimentally. The measured acoustic response of the fiber is found to be 1 order of magnitude lower than that of the bare fiber, in agreement with analytical predictions. The technique thus appears to be a promising way for desensitizing optical-fiber leads for use with fiber-optic sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Following a similar procedure, Lagakos and co-authors demonstrated analytically that, by properly choosing the glass and coating materials, and the corresponding thicknesses, it is possible to have optical fibers with reduced pressure sensitivity [28], or even insensitive to the pressure field [29,30]. They also analyzed the pressure sensitivity 145 of an optical fiber with an inner coating of silicone as a function of the external outer coating and for different frequencies [31,32,17].…”
Section: δφmentioning
confidence: 99%
“…Following a similar procedure, Lagakos and co-authors demonstrated analytically that, by properly choosing the glass and coating materials, and the corresponding thicknesses, it is possible to have optical fibers with reduced pressure sensitivity [28], or even insensitive to the pressure field [29,30]. They also analyzed the pressure sensitivity 145 of an optical fiber with an inner coating of silicone as a function of the external outer coating and for different frequencies [31,32,17].…”
Section: δφmentioning
confidence: 99%
“…Вопросам применения различных покрытий оптического волокна для защиты от акустических шумов окружающей среды посвящено большое количество исследований [6][7][8][9][10][11][12]. В этих работах изучаются полимерные [6,9], гальванические [7] и композитные [8] покрытия. Их применение требует высокой точности толщин слоев покрытий (в микрометровом диапазоне) и является довольно сложной технологической задачей.…”
unclassified
“…Несоблюдение этих требований ведет к снижению эффективности акустической изоляции [7]. В [11,12] упоминаются металлизированные покрытия для снижения акустической чувствительности.…”
unclassified
See 1 more Smart Citation